Application research of prestressed wire strand and composite mortar for flexural strengthening of T-shaped simply supported beam bridges - Xilong Zheng (Archives of Civil Engineering)
In order to validate the reinforcing effect of the prestressed wire strand-composite mortar method on actual bridges, this paper applies the reinforcing method to a T-shaped simply supported beam bridge and conducts load tests before and after the reinforcement to explore its improvement effect. A finite element model was established to obtain the theoretical calculation values of the mid-span deflection and strain of the beam under test load before and after bridge reinforcement, which serve as the basis for determining the results of static load tests. Static load tests were conducted on the original bridge, and it was determined that the stiffness of the original beam was insufficient. Through a comparative analysis of data such as deflection and strain before and after reinforcement. Under partial load and medium load, the average deflection of reinforced bridge at the mid-span section of the main beam decreases by 63% and 62% respectively, indicating that the stiffness increased significantly. Compared with before strengthening, the strain of the bridge decreased by 23% and 25.5%, indicating that the strength increased significantly. The prestressed wire strand reinforcement method can significantly have a good shrinkage effect on stress cracks in bridge structures. The composite mortar can also prolong the service life of the prestressed wire strand and has good durability performance.